Luta, resistencia e organização camponesa no alto sertão sergipano: contradições, tensões e dinâmica territorial do Programa Nacional de Alimentação Escolar (PNAE) - Santos, Fábio Ferreira (2020)
This research focuses on peasant struggles and resistance in the agrarian space, specifically in the processes of reproduction and (re)creation of peasantry in the fraction of the space known as Território do Alto Sertão Sergipano (ASS), in the interior of the state of Sergipe, Brazil. Based on the analysis of food production for the National School Feeding Programme (PNAE), it was observed that peasant organization in cooperatives and associations constitutes a mechanism of social organization of the Landless Rural Workers Movement (MST) in the face of the contradictory and unequal relations of the expansion of capitalism in the countryside. One of the ways in which the state makes itself present in SSA is through the implementation of federal programmes, starting with its territorialisation. Among them, the PNAE has direct repercussions on the reproduction of peasants since it guarantees the purchase of agricultural products originating from family-based and peasant agriculture in institutional markets (Law No. 11,947 of 2009) for official purposes of combating hunger, poverty and food and nutritional insecurity in Brazil. Therefore, the research revealed that to access these markets, the organization of peasants in associations and cooperatives is fundamental. The data collected in ASS shows that food production, which supplies the basic needs of peasant families and meets the demands of the PNAE, is possible due to the political participation of settlers and Agrarian Reform settlers in collective and community-based forms of peasant work organization, as happens in COOPAC and UNITUBA. However, it is the participation of women in the organization of production and work that gains protagonism in both instances.